Sharia Mutual Funds - Chairunnisa, Luthfia; Susanti, Fifi Zulia; Dalimunthe, Rizky Rahman (FEBI UIN Sunan Kalijaga Yogyakarta, 2024)
One of the economic activities, namely investment, is currently in great demand by people in developed countries and has now expanded to developing countries such as Indonesia. Investment is actually the activity of placing a number of funds with the intention of getting profits in the future. Investment can also be interpreted as a form of delaying the expenditure of assets for current consumption activities, to then be used for the benefit of effective and efficient production activities and within the desired deadline. So that with this delay, someone is expected to get benefits that can improve the quality and degree of his life. Until now, Islamic finance stakeholders in Indonesia have intensively disseminated types of sharia-based investments, both government and private parties. One of them is Sharia mutual funds. Just like other types of investment, we cannot directly buy this instrument without knowing clearly how the process works. Even some people must still be wondering, what's the difference with conventional mutual funds? How about growth in value? For more complete information about Islamic mutual fund investments, this research will explain.